Tradition and the individual Canadian talent - Mount, Nick (My University, 2020)
In the twenty-first century, Canadian writers have been doing something they did infrequently in the past: acknowledging and referencing the work of past Canadian writers. Although declining pedagogical and academic interest in Canadian literature has made this development hard to see, writers themselves have been quietly building upon and contributing to something that looks very much like a literary tradition. Canadian writers of course continue to read and be influenced by writers outside Canada, just as they always have: but in their own words, they are now telling us that they are reading, learning from, and responding to other Canadian writers – that there is a Canadian literary tradition that crosses generational and regional borders, and that Canadian writers (and publishers, and readers) are aware of parts of that tradition, the parts that matter to them.
Keywords: Canadian Literature; tradition; canons; influence; epigraphs; blurbs